A second remarkable case of parapatry in a Tasmanian millipede genus (Diplopoda, Polydesmida, Dalodesmidae) - Mesibov, Robert (Zookeys, 2020)
Tasmaniosoma armatum Verhoeff, 1936 and T. orientale Mesibov, 2010 are parapatric in northeast Tasmania, Australia. The parapatric boundary is ca 50 km long and mainly follows streamlines. Three sections of the boundary were intensively sampled. Two gonopod variants of T. orientale also appear to be parapatric.